Service Satisfaction About Teaching, Learning Process And Education Facilities At The Health Polytechnic Of Health Ministry Semarang - Hermien Nugraheni; Enik Sulistyowati; Triana Sri Hardjanti (Jurnal LINK, 2012)
The purpose of this study were to describe the internal customer's expectations and performance of Health Polytechnic Kemenkes Semarang, analyzing internal customer's satisfaction levels (students, lecturer and staff) to Health Polytechnic Kemenkes Semarang's services. The survey in 2009 showed that the top priority for repairs carried out are: for students, are the cost of education, for lecturers are a component of Learning Facilities, Academic Guidance and Career Development, as well as for employees are an incentive component. The survey in 2010 showed that the top priority for repairs carried out are: for students are nothing, for lecturers are Teaching Facilities, Career Development, Academic Guidance and incentives, as well as for employees are an incentive component. The survey in 2011 showed that the top priority for repairs carried out are: for students are the Education Administration, Laboratory, and Graduate Prospects, for the lecturer are teaching facilities, and incentives, as well for Employees are a component of public facilities and incentives.